Dynamic responses and robustness performance to moving boundary of double-stepped cable during deep-sea mining - Yilun Li; Shuangxi Guo; Yucheng Guo; Xiaoqi Yu; Weimin Chen; Jixiang Song (International Journal of Naval Architecture and Ocean Engineering, 2023)
As the exploration and exploitation of deep-sea oil and gas, along with promising polymetallic nodule&sulfides mining, have been developing toward ultra-deep waters, some innovative concepts of marine cable configuration suitable for ultra-deepwater are proposed, such as stepped cable, hybrid cable and double-stepped cable. For deep-water cables with complex configurations, the structural responses become more complicated due to their non-uniform structural properties. Because the distributed buoyancy modules along cable length might introduce more significant local bending segments. Moreover, the impacts of moving boundary, caused by the motions of top vessel and bottom mining vehicle, should be considered. Through combing the finite element simulations with the hydrodynamic models, the dynamic response analysis approach of ultra-deepwater cables is established in this study. Then the double-stepped cable responses, including axial tension, displacement along with the change of overall configurations caused by moving top vessel and bottom mining vehicle, are calculated. Moreover, wave propagation behaviors during cable response are comprehensively examined, and the influences of non-uniform structural properties on cable response and wave propagation are analyzed using the wave propagation theory of structure with axially varying properties based on the Bessel function. The results show that the presented double-stepped cable can provide suitable configurations during the dynamic response, which has good compliance performance and can effectively buffer its response caused by moving boundary excitation. Finally, we found that the response spatial-temporal evolutions present some interesting phenomena, such as the axially non-uniform characteristics lead to non-monotonic changes in response amplitude and wavelength, with local peaks occurring in the low-tension region, owing to the distributed buoyancy modules, along with axially-varying and discontinuous structural properties. And, there exists significant mixed effect coming from both standing waves and traveling waves.